2018
DOI: 10.1167/iovs.17-21665
|View full text |Cite
|
Sign up to set email alerts
|

Parapapillary Gamma Zone and Progression of Myopia in School Children: The Beijing Children Eye Study

Abstract: PURPOSE. To assess the development and enlargement of the parapapillary gamma zone in school children.METHODS. This school-based prospective longitudinal study included Chinese children attending grade 1 in 2011 and returning for yearly follow-up examinations until 2016. These examinations consisted of a comprehensive ocular examination with biometry and color fundus photographs. The parents underwent a standardized interview. The parapapillary gamma zone was defined as the area with visible sclera at the temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
(28 reference statements)
1
25
0
Order By: Relevance
“…[3][4][5][6][7][8] Clinical and anatomical studies have shown that the optic nerve head undergoes various changes in the process of myopic axial elongation. [9][10][11][12] These changes include an enlargement of the optic disc, the borders of which were defined by the peripapillary border tissues; a rotation of the optic disc mostly around its vertical axis; and the development of parapapillary gamma zone as BM-free parapapillary region, located mostly at the temporal optic disc side. [13][14][15][16][17][18][19][20][21] The mechanism of the development of gamma zone and to which degree the BMO accompanies the myopic enlargement of the optic disc has remained unclear so far.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] Clinical and anatomical studies have shown that the optic nerve head undergoes various changes in the process of myopic axial elongation. [9][10][11][12] These changes include an enlargement of the optic disc, the borders of which were defined by the peripapillary border tissues; a rotation of the optic disc mostly around its vertical axis; and the development of parapapillary gamma zone as BM-free parapapillary region, located mostly at the temporal optic disc side. [13][14][15][16][17][18][19][20][21] The mechanism of the development of gamma zone and to which degree the BMO accompanies the myopic enlargement of the optic disc has remained unclear so far.…”
mentioning
confidence: 99%
“…Subjects were excluded if they had any of the following: (1) a family history of glaucoma in a first-degree relative, (2) history of intraocular or refractive surgery, (3) pathologic myopia (patch chorioretinal atrophy, lacquer crack lesions, intrachoroidal cavitations, or choroidal neovascularization), (4) other evidence of retinal pathology, (5) opaque media, or (6) poor-quality OCT images because of irregular tear film or poor cooperation.…”
mentioning
confidence: 99%
“…However, Yi Dai and associates [9] reported that β-PPA and γ-PPA were associated with vertical disc diameter, and the associations between β-PPA or γ-PPA and horizontal disc diameter were unclear and not significant. Conversely, Yin Guo et al [10] demonstrated that the horizontal and vertical disc diameters were positively related to the enlargement of the parapapillary gamma zone area [10]. Since there is an oblique angle in the transpupillary view the optic disc, this observation may be influenced by the vertical tilting of the ONH in myopia.…”
Section: Discussionmentioning
confidence: 98%